ANALISIS POTENSI KERAWANAN LONGSOR BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) DI KOTA SAWAHLUNTO, SUMATERA BARAT - Saputra, adang (Universitas Negeri Padang, 2024)
West Sumatra Province has a hilly morphology so that landslides often occur in the soil layer. This research aims to analyze the potential level of landslides. Sawahlunto City, West Sumatra using GIS. The method used by the score overlay model is a land cover map, soil type map, slope slope map, rainfall map and rock type map, so that the weighting and level of vulnerability to landslides can be obtained. The research area has high, medium and low levels of landslide vulnerability in 1 sub-district, medium to high in 3 sub-districts. The potential for high landslides is in the Talawi sub-district, and a small part is in the Silungkan and Barangin sub-districts. Meanwhile, the potential for landslides is low to moderate in most of Lembah Segar sub-district.